ANALYSIS OF THE CORRECT PRONUNCIATION OF PHONETIC SYMBOLS IN ENGLISH - Kinanti; Ahmad Ridho Khualid; Yani Lubis (Cendekia Madani Nusantara, 2024)
This research aims to analyze the correct pronunciation of phonetic symbols in English by describing the Influence of Sociolinguistic and Cultural Aspects on Pronunciation, Phonetic Symbol Pronunciation, and Analysis of Proper English Phonetic Symbol Pronunciation Based on Types. The study adopts a literature review approach. Data collection involves gathering information from existing sources such as literature, journals, articles, and other relevant academic works related to the research topic. This method is employed to investigate, analyze, and synthesize previously published information on the researched subject. The research findings indicate that the first section highlights the significant impact of sociolinguistic and cultural factors on language pronunciation. It emphasizes how an individual's accent or dialect, stemming from their geographical origin, influences sound articulation. These variations occur not only between American and British English but also among non-native speakers. Their influence extends to communication practices, formal and informal settings, displaying diverse pronunciation patterns shaped by individual backgrounds and contextual influences. The second part encompasses various aspects of sound articulation, such as word stress, rhythm, intonation, and phonetic symbols. It underscores their role in altering word meanings, poetry meter, speech patterns, and emotional expression, thereby shaping communication and message delivery. Finally, English phonetic symbols are categorized and exemplified, showcasing short vowels, long vowels, diphthongs, fricative, explosive, affricate consonants, and nasals. Each category features symbols and examples illustrating the diverse phonetic sounds in English.